Outcomes of non‐surgical periodontal treatment by dental hygienists in training: impact of site‐ and patient‐level factors. Issue 4 (18th May 2013) - Preshaw, PM; Holliday, R; Law, H; Heasman, PA
Abstract Objectives To investigate the site‐ and patient‐level factors that impact on the response to non‐surgical periodontal therapy in patients with chronic periodontitis. Methods A retrospective evaluation of clinical outcomes following non‐surgical periodontal therapy delivered by dental hygienists in training was undertaken. Case notes from 195 patients with chronic periodontitis were reviewed and clinical data pre‐ and post‐treatment abstracted. Patients were categorized as 'responders' or 'non‐responders' according to defined outcome criteria, and the relationship between clinical and demographic variables and treatment outcomes was assessed. Results Overall, there was a good response to the periodontal treatment. At deep sites (those with pretreatment probing depth ≥5 mm), the mean probing depth reduction was 1.6 ± 0.9 mm. Seventy‐one (36%) patients were classified as non‐responders (indicating that at least 30% of their deep sites did not improve by at least 2 mm following treatment). The non‐responding group contained a significantly greater proportion of smokers (28%) than the responding group (16%). Plaque scores did not differ significantly between responders or non‐responders either pre‐ or post‐treatment. Regression analyses indicated that smoking status (odds ratio, OR: 2.04), mean pretreatment probing depth (OR: 1.49) and percentage of deep sites ≥5 mm at pretreatment (OR: 1.02) were significantly associated with response to treatment. Conclusion This study supports the benefits of non‐surgical therapy in the treatment of chronic periodontitis by dental hygienists in training. Better responses to treatment tend to be observed in non‐smokers and in those with less advanced periodontitis at baseline.